Facile preparation of functionalized poly(amidoamine)s with biocidal activity on wood substrates. (July 2019) - Bergamonti, Laura; Graiff, Claudia; Tegoni, Matteo; Predieri, Giovanni; Elviri, Lisa; Palanti, Sabrina; Paris, Cèline; Cappelletto, Elisa; Di Maggio, Rosa; Lottici, Pier Paolo
Graphical abstract: Highlights: Linear polyamidoamines (PAAs) are obtained by simple step-growth polymerization. PAA functionalized with siloxane network are obtained in a one pot way. The Job's plot confirms the coordination ability of PAAs towards Cu 2+ . PAAs formulations, applied on wood, are effective against xylophagous fungi and insects. Abstract: Linear poly(amidoamine)s (PAAs), functionalized in the main chain with hydroxyl and/or siloxane groups, were obtained by single step addition of primary amines (ethanolamine, 3-aminopropyltriethoxysilane) to N, N'-methylenebisacrylamide, in water or low molecular weight alcohols, without catalysts. The polymers were characterized by FTIR, Raman, 1 H and 13 C NMR, CP-MAS NMR and ESI-MS. The coordination ability of PAAs towards Cu 2+ in water was confirmed by the Job's plot method. The PAAs alone and added with Cu 2+ ions or Ag-nanoparticles were applied on wood as preservatives for fungi and insects. The siloxane hybrid formulations applied on wood are effective against C. puteana and T. versicolor fungi, even after a leaching procedure, in particular with copper addition. The PAA functionalized with OH groups are effective as wood preservatives before the leaching procedure, in particular with Ag addition. All the formulations give good results against wood-boring beetles T. holosericeus and H. bajulus ( Cerambicidae species) .